2012
DOI: 10.1111/j.1365-2249.2012.04588.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of American and European practices in the management of patients with primary immunodeficiencies

Abstract: SummaryPrimary immunodeficiency diseases (PIDs) comprise a heterogeneous group of rare disorders. This study was devised in order to compare management of these diseases in the northern hemisphere, given the variability of practice among clinicians in North America. The members of two international societies for clinical immunologists were asked about their management protocols in relation to their PID practice. An anonymous internet questionnaire, used previously for a survey of the American Academy of Allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…A similar survey was also performed with experts from the AAAAI and also ESID (48). Similar to the previous survey, the results showed that approximately half of all immunologists recommended IgG therapy for at least 5–50% of patients with SAD and there was no significant difference between the percentages of specialized and general immunologists, nor in the percentages of experts from the AAAAI and ESID, who prescribe IgG therapy.…”
Section: Therapeutic Intervention Options For Patients With Sad: Stramentioning
confidence: 99%
“…A similar survey was also performed with experts from the AAAAI and also ESID (48). Similar to the previous survey, the results showed that approximately half of all immunologists recommended IgG therapy for at least 5–50% of patients with SAD and there was no significant difference between the percentages of specialized and general immunologists, nor in the percentages of experts from the AAAAI and ESID, who prescribe IgG therapy.…”
Section: Therapeutic Intervention Options For Patients With Sad: Stramentioning
confidence: 99%
“…We found that the treatment rate in SCID is lower than CVID, XLA and HIGM. We have previously described that the percentage of immunologist recommending IgGRT to SCID patients in the USA is lower than in Europe , this difference, we hypothesized, was due to the need for more awareness of the AAAAI practice parameters guidelines among subspecialists who divide their effort among immunology and other disciplines.…”
Section: Discussionmentioning
confidence: 93%
“…Current practice is to use a broad range of dosages for these chronic neurological conditions. The same is true in primary immunodeficiencies in terms of the wide variations in dosage, treatment interval and target trough levels, as demonstrated in a 2012 survey of immunologists .…”
Section: Case Studymentioning
confidence: 85%